Assessment of the importance of technological factors in the restoration of stone structures with cracks - MOLODID, Oleksandr; BENDERSKYI, Serhii (Ways to Improve Construction Efficiency, 2025)
The article ranks 10 technological factors that influence the restoration of stone structures with cracks. The following factors were used for analysis: geometric parameters of the crack: width, depth and length; type of construction material (solid brick, hollow brick, ceramic blocks); type of repair mortar (cement, polymer) taking into account fluidity, density, shrinkage, etc.; condition of the base and its preparation, including the condition of the masonry body and the integrity of the joint filling; order of injection (filling) of the crack from bottom to top or from top to bottom; injection (filling) of cracks depending on the method of packer installation (into the crack, at an angle into the crack, at an angle outside the crack); moisture content of the structure; time and pressure of injection of the repair solution; ambient and structure temperature at the time of repair and restoration work; height of the damage (crack), accessibility to it. At the first stage, experts assessed the importance of each factor based on the Saati scale. Then, using the scoring method, the weight of each factor was determined. Thus, it has been established that the least significant factors in the restoration of cracked stone structures are the moisture content of the structure, the time and pressure of the repair solution injection, the ambient and structural temperatures at the time of repair and restoration work, the height of the damage (crack), and its accessibility. Their combined weight on the technology of restoring stone structures is 20%. Next, to verify the results obtained in determining the weight of the factors remaining for analysis, a calculation of the vector of weight coefficients (priorities) was performed. As a result, the factors were ranked. Thus, the order of injection (filling) of the crack has a weight of 20.9%; the geometric parameters of the crack – 20.4%; the condition of the base and its preparation – 19.1%; the type of construction material (solid brick, hollow brick, ceramic blocks) – 14.6%; injection (filling) of cracks depending on the method of packer installation – 12.8%; the type of repair mortar (cement, polymer) – 12.1%.